Relationship between Age, Gender, Treatment, and Disease Stage and Survival in Terminal Patients with Squamous Cell Carcinoma of the Larynx - Manfro, Gabriel (2006)
Background: The evolution of patients with laryngeal squamous cell carcinoma (SCC) after interruption of curative oncological treatment requires more in-depth understanding to facilitate more appropriate support during development of the disease. The objectives of this study were to evaluate survival and relate it to demographic, clinical, and therapeutic factors in patients with laryngeal SCC with no possibility of curative oncological treatment, and to determine the main cause for interrupting curative treatment in patients with laryngeal SCC at the Brazilian National Cancer Institute (INCA), as well as the most frequent metastasis sites. Methods: This was a retrospective study of 93 patients with laryngeal cancer treated at the palliative care unit (HC IV) from 1992 to 2003. Survival of patients was related to age, gender, type of treatment, and stage at termination of curative oncological treatment. Statistical analyses used a p value of < 0.05. The survival curve used the Kaplan- Meyer method. Results: Mean survival after interrupting curative treatment was 3.51 months. Age, gender, treatment, and disease stage were not related to survival after initiative palliative care. The main cause for treatment failure was advanced loco regional disease. The lungs were the most frequent site of distant metastases. Conclusions: Survival of patients with laryngeal SCC under palliative care was less than 4 months, and no factor was identified with any impact on survival. The most frequent cause of treatment failure was advanced locoregional disease. The most frequent site of distant metastases was the lungs.